Perinatal changes in fetal cardiac geometry and function in diabetic pregnancy at term. (8th October 2019) - Patey, O.; Carvalho, J. S.; Thilaganathan, B.
ABSTRACT: Objective: To evaluate the effect of diabetes in pregnancy on fetal and neonatal cardiac geometry and function around the time of delivery. Methods: This was a prospective study of 75 pregnant women delivering at term, comprising 54 normal pregnancies and 21 with a diagnosis of pregestational or gestational diabetes mellitus. Fetal and neonatal conventional and spectral tissue Doppler and two‐dimensional speckle‐tracking echocardiography were performed a few days before and within hours after delivery. Fetal and neonatal cardiac geometry, global myocardial deformation and performance, diastolic and systolic function and left ventricular (LV) torsion were compared between normal pregnancies and those with diabetes, and perinatal changes within the diabetes group were assessed. Results: Compared with normal pregnancies, diabetic pregnancies demonstrated significant differences in fetal ventricular geometry, myocardial deformation and cardiac function (right ventricular (RV) sphericity index, 0.56 vs 0.65; LV torsion, 2.1 °/cm vs 5.6 °/cm; LV isovolumetric relaxation time, 101 ms vs 115 ms; and RV isovolumetric contraction time, 107 ms vs 119 ms; P  < 0.001 for all). Compared with normal pregnancies, diabetic pregnancies demonstrated significant differences in neonatal cardiac parameters (mean RV sphericity index, 0.43 vs 0.55; mean LV torsion, 1.30 °/cm vs 2.78 °/cm; median LV myocardial performance index (MPI′), 0.39 vs 0.51; median RV‐MPI′, 0.34 vs 0.40; P  < 0.01 for all). Paired comparison between fetal and neonatal cardiac indices in diabetic pregnancies demonstrated that delivery resulted in a significant improvement in some, but not all, cardiac indices (mean RV sphericity index, 0.65 vs 0.55; mean LV torsion, 5.60 °/cm vs 2.78 °/cm; median RV‐MPI′, 0.51 vs 0.40; P  < 0.01 for all). Conclusions: Compared with normal term fetuses and neonates, those of diabetic women exhibit cardiac indices indicative of myocardial impairment, reflecting a response to a relatively hyperglycemic intrauterine environment with alteration in fetal loading conditions (LV preload deprivation and increased RV afterload) and adaptation to subsequent acute changes in hemodynamic load at delivery. Elucidating mechanisms that contribute to the alterations in perinatal cardiac function in diabetic pregnancy could help in refining management and developing better therapeutic strategies to reduce the risk of adverse pregnancy outcomes. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.